PENINGKATAN HASIL BELAJAR PAI SISWA KELAS X SMA NEGERI 13 MAKASSAR MELALUI PENGGUNAAN KARTU KONSEP PADA KONSEP KHALIFAH (SURAH AL BAQARAH AYAT 30) - Mujizatullah Mujizatullah (Balai Penelitian dan Pengembangan Agama Makassar, 2009)
The research aims to describe the improvement of student understandingon learning concept by using concept cards. Result shows that theuse of concept card in religion course improves the student understanding.The writer, therefore, recommend to the teacher to use concept cardtechniques in Islam course